Structure of English Locative Inversion - Adnyana, I Ketut Widi; Qomariana, Yana (Humanis, 2020)
A sentence structure involves the packaging of meaning. Words and their order decide the meaning of a sentence convey ed . This study discussed two points of problem s . The first one is locative inversion structure in sentences taken from Corpus of Contemporary American English. The other problem is the constraints of locative inversion in the English grammar. The problems are discussed based on the theory of inversion by Hewings (2005). Method used to collect the data was documentation method. The analysis was conducted using descriptive qualitative method. The result of the analysis is shown using informal method. As results, this study shows that locative inversion structure is different from canonical structures. It has a distinct feature contrasting it with canonical structure. It also has several constraints regarding subject, predicate, and salient information affecting its formation.